Dampak Halte Jak Lingko Terhadap Kenyamanan Pengguna Angkutan Umum (Studi Penelitian Tebet ECO Park) - Muhammad Ananda Bahaqi; Siti Sahara (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Jaklingko is a public transportation system in Jakarta, Indonesia that aims to provide fast and efficient intermodal transportation. This system is part of the government's efforts to reduce traffic congestion and improve public transportation services in the city. One of them is TebetEco Park which has recently been widely discussed. Not only as a park in general, Tebet Eco Park has become a tourist destination, both for the people of Jakarta and outside Jakarta. The aim of using bus stops for the surrounding area is to attract residents to use public transportation. And also as a government plan to make Jakarta a Healthy City.